Kuersetin dan Kuersetin-3-O-Glukosida dari Kulit Batang Sonneratia Alba (Lythraceae) - . Horizon; Dikdik Kurnia; Dadan Sumiarsa; Unang Supratman; Yoshihito Shiono; Betry Pujiastuti (Jurnal Kimia Valensi, 2015)
Two flavonoid compounds, quercetin (1) and quercetin-3-O-glucoside (2) have been isolated from the bark of Sonneratia alba (Lythraceae). Chemical structure of both compounds were determined on the basis of spectroscopic data and comparison with those spectra data previously reported. Compound 1 and 2 exhibited antibacterial activity against Gram-positive bacteria, Staphylococcus aureus and Streptococcus mutans with MIC values of 51.2; 48.8; 72.5; dan 100.7 µg/mL respectively.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3151